9-PAHSA Improves Cardiovascular Complications by Promoting Autophagic Flux and Reducing Myocardial Hypertrophy in Db/Db Mice - Wang, Yan-Mei; Mi, Shou-Ling; Jin, Hong; Guo, Qi-Lin; Yu, Zhong-Yu; Wang, Jian-Tao; Zhang, Xiao-Ming; Zhang, Qian; Wang, Na-Na; Huang, Yan-Yan; Zhou, Hou-Guang; Guo, Jing-Chun (Frontiers in Pharmacology, 2021)
Atherosclerotic cardiovascular disease is a common and severe complication of diabetes. There is a large need to identify the effective and safety strategies on diabetic cardiovascular disease (DCVD). 9-PAHSA is a novel endogenous fatty acid, and has been reported to reduce blood glucose levels and attenuate inflammation. We aim to evaluate the effects of 9-PAHSA on DCVD and investigate the possible mechanisms underlying it. Firstly, serum 9-PAHSA levels in human and mice subjects were detected by HPLC-MS/MS analysis. Then 9-PAHSA was synthesized and purified. The synthesized 9-PAHSA was gavaged to db/db mice with 50mg/kg for four weeks. The carotid arterial plaque and cardiac structure was assessed by ultrasound. Cardiac autophagy was tested by western blot analysis, electron microscope and iTRAQ. The results showed that 9-PAHSA, in patients with type 2 diabetes mellitus (T2DM) and diabetic mice, was significantly lower than that in non-diabetic subjects. Administration of 9-PAHSA for two weeks reduced blood glucose levels. Ultrasound observed that continue administration of 9-PAHSA for four weeks ameliorated carotid vascular calcification, and attenuated myocardial hypertrophy and dysfunction in db/db mice. Electron microscopy showed continue 9-PAHSA treatment significantly increased autolysosomes, while dramatically decreased greases in the myocardial cells of the db/db mice. Moreover, iTRAQ analysis exhibited that continue 9-PAHSA treatment upregulated BAG3 and HSPB8. Furthermore, western blot analysis confirmed that 9-PAHSA down-regulated Akt/mTOR and activated PI3KIII/BECN1 complex in diabetic myocardium. Thus, 9-PAHSA benefits DCVD in diabetic mice by ameliorating carotid vascular calcification, promoting autophagic flux and reducing myocardial hypertrophy.